PARADIGMA PENDIDIKAN ISLAM MULTIKULTURAL DI ERA MELENIAL; SEBUAH KAJIAN DISKURTIF - Ahmad Fauzi (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2018)
Sociologically, multicultural education is an attempt to preserve Islamic values as the vision of Islam rahmatanlil'alamin. Therefore, Islamic education today, faced with various increasingly crucial challenges, this view, cannot be separated from the atmosphere of modernization and globalization. Thus the presence of Islamic education is required to play its role dynamically and is expected to be able to provide change in the midst of a pluralistic society. Thus to build Islamic education in Indonesia which can bring a universal vision, it is necessary to have a paradigm of multicultural Islamic education, by promoting several principles, including; maintaining harmony, peace of mutual respect and liberation, not the other way around as domestication and social taming (social and cultural domestication). In this context, education is referred to as social enlightenment. Therefore, the effort to build the paradigm of Islamic education is a necessity, this can be done by restoring the social values of Islamic education universally besides being dynamic (inclusive), through several stages, namely a) building inclusive awareness by transmitting the entire system socio-religious values such as ketauhidan, tolerance and justice in the curriculum structure (culture domination and control). b) reconstructing the paradigm of Islamic education from the point of view of indoctrination to participatory, c) changing the ideological paradigm into scientific by giving the human mind the freedom to study and develop knowledge through His guidance.